1993
DOI: 10.1007/bf01087914
|View full text |Cite
|
Sign up to set email alerts
|

Protein, calcium, iron, and amino acid content of selected wild and domesticated cultivars of finger millet

Abstract: Two wild and eight domesticated cultivars of finger millet were analyzed to determine their proximate composition and calcium, iron, and amino acid content. Wide variations were observed in the protein (mean values ranged from 7.5 to 11.7%), calcium (376 to 515 mg/100 g), and iron (3.7 to 6.8 mg/100 g) content of the wild and domesticated cultivars. A wild progenitor of finger millet, E coracana subsp. africana was significantly higher in protein than four of the six domesticated accessions analyzed. The calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 11 publications
1
53
3
Order By: Relevance
“…Rice grains contain 10 mg/100 g of calcium, whereas some genotypes of finger millet contain relatively high amounts of calcium in their seeds (376-515 mg/100 g), which is far above levels seen in other cereals and millets (Barbeau and Hilu, 1993;Panwar et al, 2010). Though calcium is important for maintaining human health, few research efforts have been directed toward understanding the mechanisms of calcium accumulation in developing cereal grains.…”
Section: Discussionmentioning
confidence: 99%
“…Rice grains contain 10 mg/100 g of calcium, whereas some genotypes of finger millet contain relatively high amounts of calcium in their seeds (376-515 mg/100 g), which is far above levels seen in other cereals and millets (Barbeau and Hilu, 1993;Panwar et al, 2010). Though calcium is important for maintaining human health, few research efforts have been directed toward understanding the mechanisms of calcium accumulation in developing cereal grains.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they may be harvestable during seasons when other foods are scarce (Johns, 1994). Finger millet (Eleusine coracana), for example, suffers relatively few diseases and pests, is tolerant to soil moisture stress and has excellent storage qualities ( Barbeau and Hilu, 1993). It also has a growth cycle of only three months and thus can provide two harvests a year.…”
Section: Use Of Indigenous Food Cropsmentioning
confidence: 99%
“…For example, finger millet has been found to be a good nutrient source with relatively high calcium content ( Barbeau and Hilu, 1993 (Akhtar, 1987). It has also been found that an increased incidence of chronic diseases, such as diabetes, is experienced by many indigenous people as they adopt western diets and lifestyles.…”
Section: Use Of Indigenous Food Cropsmentioning
confidence: 99%
“…The world's largest contribution to selections was in countries where common millet is most grown, such as India and USA (Manoharan & Sivasubramanian 1982, Baltensperger 2002, Karam et al 2004, Upadhyaya et al 2011. Crossing of various genotypes and examination of a large number of qualitative and quantitative indicators has been the subject of many studies (Barbeau & Hilu 1993, Zeller 2000, Heyduck et al 2008, Cho et al 2010, Hunt et al 2011. The aim of this study was to determine millet genotypes productivity for grain, based on regular and stubble crop on yield and individual agro-biological traits.…”
Section: Acknowledgementsmentioning
confidence: 99%